2013
DOI: 10.1128/genomea.00253-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Canine-Origin H3N2 Feline Influenza Virus Isolated from Domestic Cats in South Korea

Abstract: A canine-origin Korean H3N2 feline influenza virus (FIV), A/feline/Korea/01/2010 (H3N2), was isolated in 2010 from a dead cat with severe respiratory disease. Here, we report the first complete genome sequence of this virus, containing 3′ and 5′ noncoding regions, which will help elucidate the molecular basis of the pathogenesis, transmission, and evolution of FIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…6), so this suggests that the infectivity difference between NLFK and Mpf cells was likely not due to receptor differences. These results were interesting because ferrets are susceptible to influenza and are used as a model for human virus infection and transmission (71), and there is already evidence that CIV H3N2 can infect cats (72,73). Additionally, a previous study showed that EIV replicated in the upper respiratory tract in live ferrets but was restricted in the lungs (74).…”
Section: Discussionmentioning
confidence: 92%
“…6), so this suggests that the infectivity difference between NLFK and Mpf cells was likely not due to receptor differences. These results were interesting because ferrets are susceptible to influenza and are used as a model for human virus infection and transmission (71), and there is already evidence that CIV H3N2 can infect cats (72,73). Additionally, a previous study showed that EIV replicated in the upper respiratory tract in live ferrets but was restricted in the lungs (74).…”
Section: Discussionmentioning
confidence: 92%
“…1A and B). To validate these HA and NA ssNCR sequence logos, we also examined the NCR sequences from the literature, which were determined accurately by specific NCRsequencing methods (27,(32)(33)(34)(35)(36), and compared them with the sequence logos generated from the bioinformatics analysis (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…H3N2 FIV isolates were included in the data set for the origin and genotyping analysis. Although H3N2 FIV has been isolated in cats, it is essentially H3N2 CIV (Park et al., ; Zhu et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, a veterinarian was infected with a low pathogenic avian influenza virus H7N2, which was also isolated from a cat shelter in New York City (Belser et al., ). Canines carrying avian‐origin H3N2 CIV have also the potential to transmit the virus to other species in frequent close contact such as cats (Jeoung et al., ; Park et al., ). Although no human infections have yet been reported with H3N2 CIVs, more and more new H3N2 CIV cases are being reported in the USA and Eastern Asia and it may be a matter of time before human infections are reported or passed as unrecognized cases.…”
Section: Introductionmentioning
confidence: 99%